The relationship between measures of physical performance in preoperative oesophageal cancer patients. (4th May 2021) - Eriksson, Frances; Trölle, Ulrika; Becovic, Suada; Hermansson, Michael; Olsén, Monika Fagevik
Abstract: Background and aim: Preoperative testing of physical performance is common for patients undergoing an esophagectomy, but little evidence exists suggesting which measures are most suitable. This study compared outcome measures currently used at participating hospitals (spirometry, cycle ergometer test) against other validated tests – Maximal Inspiratory Pressure (MIP), Maximal Expiratory Pressure (MEP), Timed Up and Go (TUG), 6 Minute Walk Test (6MWT), heel raise test, shoulder abduction test, Timed Stands Test (TST) and handgrip strength. Methods: 109 patients were recruited from three university hospitals in Sweden. Participants were tested using a protocol testing respiratory and peripheral muscle strength, lung function, endurance and fitness. Results: There were strong correlations between the cycle ergometer and grip strength ( r  = 0.619), 6MWT ( r  = 0.572), MIP ( r  = 0.619) and MEP ( r  = 0.529). A strong correlation was also seen between spirometry and grip strength ( r  = 0.508–0.574). A moderate correlation was found between spirometry, MIP ( r  = 0.405–0.470) and MEP ( r  = 0.366–0.452), the cycle ergometer, TUG ( r  = −0.321) and TST ( r  = −0.308) and between 6MWT and PEF ( r  = −0.333). Conclusion: The strong correlations between different measures suggest that in cases where the standard tests are inadvisable or impractical, simple tests like grip strength and 6MWT could be used instead.